Experimental studies on the absorption, swelling and erosion performance of hybrid woven Kevlar/hemp reinforced epoxy composites - Sangilimuthukumar Jeyaguru; Senthil Muthu Kumar Thiagamani; Sanjay Mavinkere Rangappa; Suchart Siengchin (eXPRESS Polymer Letters, 2023)
Hybridization of natural and synthetic fibers in a single composite material can be made by several means, and one of the best methods is the intra-ply in which both fibers are woven within a single layer. Through hybridization, the advantages of one type of fiber can improve the limitations of the other. Further the blending of natural and synthetic fibers leads to the fabrication of composites with higher mechanical performance. Hence, this work focuses on the fabrication of intra-ply Kevlar and hemp fiber reinforced epoxy hybrid composites with different weaving patterns such as plain weave, basket weave, and twill weave type. Yarns were woven by handloom technique to make intra-ply Kevlar and hemp fiber mats, and the composites were fabricated by compression molding. The water absorption, thickness swelling, and solid particle erosion characteristics of the composites were examined. The results of the experiments showed that the hemp fiber composites exhibited the least resistance (8.45% change in absorption and 4.34% change in thickness) towards the absorption and swelling, whereas pure epoxy (0.67% change in absorption and 0.31% change in thickness) and Kevlar (2.67% change in absorption and 1.67% change in thickness) composites possessed higher resistance. The absorption and swelling performance of all other hybrids was found to be in between the hemp and Kevlar composites hence proving the effectiveness of the hybridization. Further, Taguchi’s experimental design results indicated that the basket weave type hybrid composites had a minimal erosion rate for 2 minutes of exposure duration and an impact angle of 90°. The morphological analysis of the eroded surfaces of composites revealed the presence of micro cavities, broken fibers, crater formation, and microcracks.